AN INVESTIGATION INTO SOME DEMOGRAPHIC INDICES IN ISPHAHAN, 1974 - Dr. Kazem Mohammad; Dr. Hossein Malek-Afzali; Dr. Manoochehr Asgari (Tehran University of Medical Sciences, 1979)
In this study which was carried out in 1974 in the province of Isphahan a total of 23,273 individuals in the cities, and 18,671 individuals in the villages of the same area were studied. Results show that the median age in rural area is 16 and in urban area is 18 years. The birth rate in rural is 27.7 per thousand were as the same rate in urban area is 40.2 per thousand. Similarly the general fertility rate is 141.8 per thousand in rural and 232.5 per thousand in urban. The mean birth/pregnancy index for women in their fertile period is 8.2 in rural and 9.5 in urban area.